COATING ON COMPOSITE PISTON HEAD WITH ZIRCONIA POWDER USING SPRAY THERMAL COATING TO INCREASE MECHANICAL STRENGTH AND FUEL SAVING - Solechan MT (Universitas Muhammadiyah Semarang, 2023)
Motor vehicle pistons are often damaged. Most of the damage to the piston is worn and broken. Waste aluminum piston added with SiC can be used for the manufacture of new pistons, but low heat resistance, easy wear and high abrasion. How to overcome these shortcomings, carried out the process of coating the composite piston head with zirconia powder using a thermal spray coating. This process is able to improve mechanical properties and save fuel, but its strength is still below the standard strength of the original piston. The research objective is to analyze the effect of the composition of the material mixture, the number of coatings and the firing distance on the composite piston head on mechanical strength and fuel saving. The research method is to coat the composite piston head using a thermal spray coating using zirconia powder. The research variable is by varying the composition of the piston material mixture, the number of coatings and the firing distance of the coating. Coating material of zirconia or for grain size of 20 µm. Optimal results are obtained by the composition of the piston mixture on the P3 code specimen, coated 5 times, and the firing range is 8 cm. For hardness of 77.29 HRV, wear of 1.50E-03 mm2/Kg and fuel saving of 4.36% compared to the original piston.